A 3D printing method for preparing a porous structure ceramic bond diamond superhard material

CN122771771APending Publication Date: 2026-09-18UNIV OF SCI & TECH BEIJING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610777280.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-01
Publication Date
2026-09-18

AI Technical Summary

Technical Problem

现有技术中,虽有采用3D打印制备陶瓷结合剂金刚石工具的尝试,但多存在金刚石分散不均匀、浆料稳定性不足、干燥和固化裂纹、研磨锋利度下降、寿命不稳定等问题,导致晶圆表面粗糙度大且不均匀、砂轮使用寿命短,无法满足半导体晶圆减薄的严苛要求

Benefits of technology

[0025] (1) Ceramic-bonded diamond superhard materials were prepared using 3D printing technology with ink direct writing (DIW). Compared with selective laser sintering (SLS) 3D printing technology, there are no special requirements for powder particle size and shape, commonly used industrial raw materials can be used, and the printing time is short and the efficiency is high, so the manufacturing cost is low. Compared with photopolymerization methods such as digital light processing (DLP), the slurry has a high solid content, which can improve manufacturing efficiency and reduce the deformation of parts after debinding and sintering. Compared with the traditional molding process using pore-forming agents, the printable porosity is high, the pore size is large, and the pore distribution and size are uniform. The porous structure can significantly improve the heat dissipation and chip removal of the grinding wheel, avoid wafer damage caused by heat accumulation during processing, reduce the friction between the abrasive and the wafer surface, reduce the thickness of the damage layer, and improve the processing quality;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122771771A_ABST
    Figure CN122771771A_ABST
Patent Text Reader

Abstract

The application provides a 3D printing preparation method of a porous structure ceramic bond diamond superhard material, relates to the technical field of superhard material tools and semiconductor processing, and comprises the following steps: vacuum heating and then acid washing of diamond powder, ultrasonic dispersion and filtration to obtain dispersed diamond powder; preparing an aqueous organic binder containing hydroxyethyl cellulose, hydroxypropyl methyl cellulose, glycerol and polyether modified silicone oil; ball milling of a ceramic bond, a dispersant and a silane coupling agent, then adding the dispersed diamond powder and the organic binder, and continuously ball milling to obtain a ball milling slurry, vacuum heating to adjust the viscosity to obtain a printing slurry; layer-by-layer printing according to a preset porous structure model, drying and solidification to obtain a green body; and defatting and sintering of the green body to obtain the diamond superhard material. The diamond superhard material is composed of diamond particles, a ceramic bond and pores, can realize high sharpness and high wear resistance of a grinding wheel, meets the severe requirements of wafer thinning and polishing, and improves processing efficiency and surface quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of superhard material tools and semiconductor processing technology, and in particular to a 3D printing preparation method for a porous ceramic-bonded diamond superhard material. Background Technology

[0002] As the semiconductor industry moves towards higher integration and miniaturization, 3D packaging technology is widely used, placing higher demands on the precision, efficiency, and surface quality of wafer thinning processes. Wafer thinning is a key process in semiconductor packaging, requiring the wafer thickness to be reduced to a specified size (≤100μm in some scenarios). This necessitates processing tools with high hardness, high wear resistance, good heat dissipation, and low damage characteristics.

[0003] Currently, commonly used wafer thinning tools in the semiconductor field are mostly resin-bonded or traditional ceramic-bonded diamond wheels. Resin-bonded wheels suffer from poor wear resistance, easy diamond abrasive shedding, and short service life. Furthermore, they are prone to heat accumulation during processing, leading to defects such as cracks and excessively thick damage layers on the wafer surface. Ceramic-bonded diamond wheels, on the other hand, possess excellent self-sharpening properties and high heat resistance, making them widely used in wafer thinning. However, traditional ceramic-bonded diamond wheels are often produced using a molding process, where pores are created by the decomposition of pore-forming agents during sintering. This makes it difficult to produce a uniform porous structure, resulting in low porosity, poor heat dissipation and chip removal, and uneven molding density. Consequently, they exhibit instability in high-precision wafer processing.

[0004] 3D printing, as an additive manufacturing technology, boasts advantages such as high forming precision, the ability to fabricate complex structures, and high material utilization, and has been gradually applied to the fabrication of superhard material tools. While there have been attempts to use 3D printing to prepare ceramic-bonded diamond tools, these efforts often suffer from problems such as uneven diamond dispersion, insufficient slurry stability, drying and curing cracks, decreased grinding sharpness, and unstable lifespan. This results in large and uneven wafer surface roughness and short grinding wheel lifespan, failing to meet the stringent requirements for semiconductor wafer thinning.

[0005] Therefore, developing a porous ceramic-bonded diamond grinding wheel with uniform diamond dispersion, a porous structure, controllable heat dissipation and chip removal performance, and continuous, stable, and high-efficiency grinding capability, suitable for high-precision thinning of semiconductor wafers, has become a pressing technical problem to be solved in this field. Summary of the Invention

[0006] To address the problems existing in the prior art, this invention provides a 3D printing method for preparing porous ceramic-bonded diamond superhard materials. The diamond superhard material consists of diamond particles, a ceramic binder, and pores. The pores are macroscopic pores constructed during the 3D printing process. Through diamond dispersion, slurry preparation, and 3D printing to prepare a controllable porous structure, combined with optimized processes such as drying, degreasing, and sintering, the grinding wheel achieves high sharpness, high wear resistance, and good heat dissipation, meeting the stringent requirements of wafer thinning and polishing, and improving processing efficiency and surface quality.

[0007] Based on the above principles, this invention provides a 3D printing method for preparing porous ceramic-bonded diamond superhard materials, the method comprising the following steps:

[0008] (1) Dispersing diamond powder: The diamond powder is vacuum heated at a temperature of 450-550℃ and a vacuum degree of 300-700Pa for 30-60 minutes. It is stirred with a mixed acid containing perchloric acid and nitric acid at 200-210℃ for 4-5 hours. After treatment, it is washed with water. Based on the weight of the diamond powder, 0.2-0.5wt.% of dispersant sodium hexametaphosphate, 0.2-0.5wt.% of silane coupling agent and 10-50 times the amount of water are added. The mixture is ultrasonically dispersed for 30-60 minutes and then filtered out to obtain dispersed diamond powder.

[0009] (2) Preparation of organic binder solution: The main ingredient hydroxyethyl cellulose, the thickener hydroxypropyl methyl cellulose, the lubricant glycerin and the defoamer polyether modified silicone oil are added to deionized water and dispersed evenly to obtain a water-based organic binder for 3D printing.

[0010] (3) Ball milling slurry: Add 45-55 wt.% ceramic binder, 0.2-0.5 wt.% dispersant sodium hexametaphosphate, 0.8-1.5 wt.% silane coupling agent and the balance deionized water to a mechanical ball mill and ball mill for 16-24 h to obtain ball milling material; add the diamond powder filtered out in step (1) to the ball milling material, add the organic binder solution prepared in step (2), and continue ball milling for 1-2 h to obtain ball milling slurry;

[0011] (4) Adjusting viscosity: After adjusting the viscosity of the ball mill slurry from step (3) by vacuum heating, printing slurry is obtained;

[0012] (5) Printing and shaping: The printing paste obtained in step (4) is fed into the ink direct writing 3D printer. The printing parameters are set as follows: nozzle diameter 0.5-0.8mm, printing speed 10-15mm / s, layer height 0.4-0.6mm, extrusion pressure 0.4-0.6MPa. The printing is carried out layer by layer according to the preset 3D printing porous structure model. After printing, it is placed in an environment with a relative humidity of 50-60% at 25-35℃ for 1-2 days. Then the humidity is adjusted to 35-45% and placed for another 1-2 days. Then the temperature is adjusted to 60-80℃ and dried for 1-2 days to complete the curing and obtain ceramic binder diamond printing green body.

[0013] (6) Degreasing and sintering: The green body from step (5) is placed in a high-temperature furnace and protected by nitrogen or argon. First, degreasing is performed by heating at a rate of 2-5℃ / min to 500-550℃ and holding for 2-4 hours to remove the binder in the green body. Then, sintering is performed by heating at a rate of 3-5℃ / min to 600-900℃ and holding for 1-2 hours. Finally, the body is cooled to room temperature at a rate of 3-5℃ / min to obtain the porous ceramic bonded diamond superhard material.

[0014] Preferably, in step (1), the diamond powder has a particle size of 300 mesh or more, particularly 2000 mesh or more.

[0015] Preferably, in step (1), the mixed acid consists of pure perchloric acid and nitric acid, with a volume ratio of 4:1, and the mass of the mixed acid is 3-10 times the mass of the diamond powder.

[0016] Preferably, in step (2), the mass concentration of each component in the water-based organic binder is: 2.0-6.0 wt.% hydroxyethyl cellulose, 0.5-1.0 wt.% hydroxypropyl methyl cellulose, 1.2-1.8 wt.% glycerol, 0.6-1.0 wt.% polyether-modified silicone oil, and the balance is deionized water.

[0017] Preferably, in step (3), the mass ratio of diamond powder, ceramic binder and organic binder solution in the ball milling slurry is 1: (1-4): (0.5-2.5).

[0018] Preferably, in step (4), the vacuum heating conditions are: heating the ball mill slurry to 50-80°C under a vacuum of 10-50 kPa.

[0019] Preferably, in step (4), after vacuum heating the ball mill slurry from step (3), intermittent sampling is performed to test the viscosity, which reaches 3000-5000 Pa. . s, to obtain the printing paste.

[0020] Preferably, in step (5), the porosity of the 3D printed porous structure model is 30-70%, preferably 40-60%; the pore size of the 3D printed porous structure model is 0.1-1.0 mm, preferably 0.3-0.7 mm.

[0021] Preferably, in step (5), the 3D printed porous structure model is a cuboid or a cuboid curved into an arc shape, with the printing path along a direction at a 45-degree angle to the long side, and the paths of adjacent layers perpendicular to each other. Preferably, the dimensions of the cuboid are: length 15-25mm, width 3-4mm, height 9-11mm, and the curvature radius of the arc-shaped cuboid is 150mm or 100mm.

[0022] The present invention also provides porous ceramic-bonded diamond superhard materials prepared by the method.

[0023] The present invention also provides a wafer thinning grinding wheel, which is obtained by bonding the porous ceramic binder diamond superhard material to an aluminum substrate with an adhesive, and then by dimension trimming and dynamic balancing after curing.

[0024] Compared with the prior art, the advantages of the present invention are:

[0025] (1) Ceramic-bonded diamond superhard materials were prepared using 3D printing technology with ink direct writing (DIW). Compared with selective laser sintering (SLS) 3D printing technology, there are no special requirements for powder particle size and shape, commonly used industrial raw materials can be used, and the printing time is short and the efficiency is high, so the manufacturing cost is low. Compared with photopolymerization methods such as digital light processing (DLP), the slurry has a high solid content, which can improve manufacturing efficiency and reduce the deformation of parts after debinding and sintering. Compared with the traditional molding process using pore-forming agents, the printable porosity is high, the pore size is large, and the pore distribution and size are uniform. The porous structure can significantly improve the heat dissipation and chip removal of the grinding wheel, avoid wafer damage caused by heat accumulation during processing, reduce the friction between the abrasive and the wafer surface, reduce the thickness of the damage layer, and improve the processing quality;

[0026] (2) This invention first roughens the surface of diamond particles through micro-oxidation, and then achieves a triple synergistic effect of "activation + dispersion + coupling" by using the surfactant sodium hexametaphosphate and the coupling agent silane coupling agent. This results in a comprehensive effect of synergistic dispersion, interface strengthening, and stability improvement, thereby improving the roughness of the processed surface. At the same time, it enhances the bonding force between diamond particles and ceramic binder, prevents abrasive detachment, and improves the sharpness, wear resistance, and service life of the grinding wheel.

[0027] (3) This invention employs a progressive ball milling process. First, the ceramic binder is ball-milled for an extended period to ensure thorough and uniform mixing of all components. The ball milling process further refines the powder, improving the uniformity of the material composition and enhancing sintering activity, which helps lower the sintering temperature. Then, ultrasonically dispersed diamond powder is added and ball-milled for a shorter time to minimize damage to the diamond particles, maintain their particle size and strength, and achieve precise control over the grinding effect. Additionally, this process reduces impurities introduced during the grinding of the ball mill jar and balls by the superhard diamond, improving the accuracy of the designed composition and the material properties.

[0028] (4) The three-stage gradient environmental drying process of the present invention controls the drying rate in a specific temperature and humidity environment, avoiding the problem of cracking caused by direct drying of the printed green block. The degreasing process slowly decomposes and removes organic matter through slow heating, ensuring that the organic matter is completely decomposed and removed before the sintering temperature, thus avoiding problems such as bubbling and cracking caused by the sintering process. Therefore, the present invention achieves crack-free and non-deformed printed blocks by controlling the drying and degreasing processes, meeting the quality requirements of grinding wheels. Attached Figure Description

[0029] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0030] Figure 1 Photos of diamond powder settling for 2 hours after different treatments;

[0031] Figure 2 Photographs of defective 3D-printed samples when the composition of the organic binder in the slurry is unsuitable;

[0032] Figure 3 Photographs of defective 3D-printed samples with air bubbles in the slurry;

[0033] Figure 4 Photos of defective 3D-printed samples when the slurry viscosity is unsuitable;

[0034] Figure 5 Photographs of defective samples resulting from excessively rapid drying of 3D printed green bodies;

[0035] Figure 6 This is a photograph of a sample block from Embodiment 1 of the present invention;

[0036] Figure 7 This is a photograph of a sample block from Embodiment 2 of the present invention;

[0037] Figure 8This is a photograph of a sample block from Embodiment 3 of the present invention;

[0038] Figure 9 This is a photograph of a sample block from Embodiment 4 of the present invention;

[0039] Figure 10 This is a photograph of a sample block from Embodiment 5 of the present invention;

[0040] Figure 11 Photograph of the thinned grinding wheel in Embodiment 4 of the present invention;

[0041] Figure 12 Photograph of the thinned grinding wheel in Embodiment 5 of the present invention;

[0042] Figure 13 This is a photograph of a sample block from Comparative Example 1 of the present invention;

[0043] Figure 14 This is a photograph of a sample block from Comparative Example 2 of the present invention. Detailed Implementation

[0044] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.

[0045] Ceramic-bonded diamond wheels possess excellent self-sharpening properties and high heat resistance, leading to their increasingly widespread application in wafer thinning wheels. Ceramic-bonded diamond wheels consist of three basic elements: diamond particles, a ceramic binder, and pores. Conventional preparation methods utilize powder metallurgy, involving the mixing, pressing, and sintering of diamond powder, ceramic powder, and a pore-forming agent. However, accurately controlling the number, size, and distribution of pores using a pore-forming agent is relatively difficult. The emergence of 3D printing technology provides an excellent solution to this problem. 3D printing techniques such as SLS, DLP, and DIW have been used for the fabrication of ceramic-bonded diamond tools. Among these methods, DIW offers advantages such as good powder compatibility, high printing efficiency, and low manufacturing cost, making it particularly suitable for industrial production. Therefore, this invention employs DIW 3D printing technology to prepare ceramic-bonded diamond wheels.

[0046] This invention provides a 3D printing method for preparing a porous ceramic-bonded diamond superhard material. The diamond superhard material consists of diamond particles, a ceramic binder, and pores, wherein the pores are macroscopic pores constructed during the 3D printing process. The preparation method includes the following steps:

[0047] (1) Dispersing diamond powder: The diamond powder is vacuum heated at a temperature of 450-550℃ and a vacuum degree of 300-700Pa for 30-60 minutes. A mixture of pure perchloric acid and nitric acid (volume ratio 4:1) is stirred at 200-210℃ for 4-5 hours. The mass of the mixed acid is 3-10 times the mass of the diamond powder. After treatment, the powder is washed with water and filtered out. Then, 0.2-0.5 wt.% of dispersant sodium hexametaphosphate, 0.2-0.5 wt.% of silane coupling agent and 10-50 times the mass of water are added to the ultrasonic dispersion equipment based on the mass of the diamond powder. The mixture is ultrasonically dispersed for 30-60 minutes and then filtered out to obtain dispersed diamond powder.

[0048] This step serves two purposes: first, to increase the surface roughness of the diamond particles; and second, to disperse the diamond particles. By vacuum heating at 450-550℃ and a vacuum degree of 300-700Pa for 30-60 minutes, slight oxidation occurs on the surface of the diamond particles. The choice of temperature and vacuum degree is crucial, as it is related to the size of the diamond particles. For coarser 320-mesh diamonds, a higher temperature of 550℃ and a lower vacuum degree of 700Pa can be selected; for finer 2000-mesh diamonds, a medium temperature of 500℃ and a medium vacuum degree of 500Pa can be selected; and for even finer 6000-mesh diamond particles, a lower temperature of 450℃ and a higher vacuum degree of 300Pa can be selected. Then, a mixture of pure chloric acid and nitric acid (volume ratio 4:1), 3-10 times the mass of the diamond powder, is stirred at 200-210℃ for 4-5 hours to clean the surface of the diamond particles and remove residual carbon formed by micro-oxidation, thus achieving activation. In this way, when ultrasonically dispersed with dispersant sodium hexametaphosphate and silane coupling agent, the dispersant and coupling agent can be better adsorbed. In this step, micro-oxidation and mixed acid activate the diamond surface, the surfactant sodium hexametaphosphate achieves dispersion, and the silane coupling agent achieves affinity with subsequent organic matter, achieving a triple synergistic effect of "activation + dispersion + coupling", resulting in comprehensive effects such as synergistic dispersion, interface strengthening, and improved stability.

[0049] Figure 1 These are photos of 6000-mesh diamond powder treated with different methods after settling in water for 2 hours. From left to right: (a) micro-oxidation activation + sodium hexametaphosphate dispersant + silane coupling agent, (b) sodium hexametaphosphate dispersant + silane coupling agent, (c) sodium metaphosphate dispersant, (d) micro-oxidation activation, and (e) no treatment. It can be seen that (a) is the powder treated with a triple process of "activation + dispersion + coupling," and its dispersion and suspension effects are significantly better than the other cases. This better dispersion effect improves the surface roughness of the machined surface. Furthermore, it ultimately enhances the bonding force between the diamond particles and the ceramic binder, preventing abrasive detachment and improving the sharpness, wear resistance, and service life of the grinding wheel.

[0050] Since the primary application of this invention is the thinning and polishing of semiconductor wafers, the diamond powder particle size is 300 mesh or larger, especially 2000 mesh or larger. The coarser particle size is mainly used for rapid polishing to remove a certain thickness from the wafer, while the finer particle size is mainly used for polishing the surface, reducing the depth of the damage layer on the wafer surface. Currently, the finest diamond powder particle size used is 8000 mesh or even higher.

[0051] (2) Preparation of organic binder solution: The water-based organic binder for 3D printing includes the main material hydroxyethyl cellulose (HEC), the thickener hydroxypropyl methyl cellulose (HPMC), the lubricant glycerin, the defoamer polyether modified silicone oil and deionized water. The concentrations of each component are as follows: 2.0-6.0 wt.%, 0.5-1.0 wt.%, 1.2-1.8 wt.%, 0.6-1.0 wt.%, and the remainder is deionized water.

[0052] One of the core components of DIW (Digital-Induced Welding) is the organic binder solution, whose components affect the powder solids content (powder loading in the solution), printing ability, and green body strength after curing. Since this invention relates to ceramic-bonded diamond superhard materials, a non-toxic and environmentally friendly aqueous solution system is used. Polyvinyl alcohol (PVA) and polyethylene glycol (PEG) are commonly used organic binders, but they have poor forming power. This invention selects HEC and HPMC as the main components. HEC has good water solubility, dissolves rapidly in cold water, and has excellent stability. Its aqueous solution has high viscosity and thickening effect, effectively improving the viscosity and stability of the product. Furthermore, HEC has excellent suspending ability, suspending solid particles in water and preventing sedimentation. HPMC swells in cold water to form a clear or slightly turbid colloidal solution, possessing thickening, film-forming, water-retaining, and binding properties, and is chemically stable. HPMC has a wide range of applications. In the pharmaceutical industry, it is commonly used as a binder, disintegrant, sustained-release matrix material for tablets, and capsule material. In the food industry, it is used as a thickener and stabilizer. In the building materials industry, it is an important water-retaining agent and thickener.

[0053] Figure 2These are photographs of defective 3D printed samples when the organic binder composition in the slurry is unsuitable. In sample (a), the organic binder used only HEC (specifically, the organic binder includes HEC, lubricant glycerin, defoamer polyether-modified silicone oil, and deionized water, with concentrations of 6.0 wt.%, 1.5 wt.%, 0.8 wt.%, and the remainder deionized water, respectively). Due to insufficient slurry consistency, the printed product in Figure (a) lacks the ability to maintain its shape and is prone to collapse. In sample (b), the organic binder used only HPMC (specifically, the organic binder includes HPMC, lubricant glycerin, defoamer polyether-modified silicone oil, and deionized water, with concentrations of 1.0 wt.%, 1.5 wt.%, 0.8 wt.%, and the remainder deionized water, respectively). Due to the excessive viscosity of the slurry, extrusion is difficult, and the printed product in Figure (b) is difficult to form.

[0054] Combining the characteristics of HEC and HPMC, this invention uses HEC as the main component and HPMC as the auxiliary component, making them the main components of the organic binder. A mass ratio of 4:1 to 6:1 between the two has a good overall effect, which is that it can maintain a good printing shape, load more powder, and achieve a high solids content (above 50 vol%) in the slurry.

[0055] In addition, to reduce friction and lower extrusion pressure during the slurry extrusion process, thus ensuring a smoother extrusion process, the organic binder of this invention also incorporates glycerol as a lubricant. For example, without glycerol, the extrusion pressure of a slurry with 50% solids content is close to the upper limit of compressed air pressure, 0.6 MPa; after adding glycerol, the extrusion pressure decreases to 0.4 MPa. If the amount of glycerol is too small, the lubrication effect is not significant; if the amount of glycerol is too large, the slurry becomes thinner, reducing its shape-holding ability.

[0056] However, during the subsequent mixing of the slurry, air bubbles may be incorporated into the slurry, causing temporary interruptions in extrusion and slurry ejection during printing. Figure 3 As shown, the printing process becomes unstable, so an appropriate amount of polyether-modified silicone oil is added as a defoamer. Polyether-modified silicone oil, as a defoamer, combines the hydrophobicity of organosilicon and the hydrophilicity of polyether, forming a film on the liquid surface to inhibit foam generation and development, while enhancing compatibility with the liquid and improving the defoaming effect. In practical applications, it can effectively reduce surface tension, stabilize bubble size and dispersion, and significantly improve liquid stability; in addition, its high-temperature resistance and corrosion resistance meet the needs of diverse industries. The amount of defoamer added is determined by considering the solid content of the powder and the amount of glycerin added, as glycerin itself also has a certain defoaming effect. Adding too much defoamer will lead to insufficient shape retention and collapse; adding too little will result in poor defoaming effect.

[0057] (3) Ball milling slurry: Add 45-55 wt.% ceramic binder, 0.2-0.5 wt.% dispersant sodium hexametaphosphate, 0.8-1.5 wt.% silane coupling agent and deionized water (balance) to a mechanical ball mill and ball mill for 16-24 h to obtain ball milling material; add the diamond powder filtered out in step (1) to the ball milling material, add the organic binder solution prepared in step (2), and continue ball milling for 1-2 h to obtain ball milling slurry. The mass ratio of diamond powder, ceramic binder and organic binder solution added is 1:(1-4):(0.5-2.5).

[0058] Since diamond is currently the hardest superhard material, prolonged ball milling can cause significant wear on the milling jar and grinding balls. The worn-off debris can also contaminate the material, altering its composition and ultimately affecting its properties, leading to unstable and unreliable tool operation. Therefore, this invention first employs a prolonged ball milling process (16-24 hours) on the ceramic binder component to ensure uniform composition and reduced particle size. This enhances the sintering process and promotes uniform final material properties, while also contributing to improved material performance through grain refinement. Then, diamond powder and an organic binder solution are added, followed by a short ball milling period of 1-2 hours. This ensures thorough and uniform mixing of the diamond powder, organic binder, and ceramic powder, while minimizing wear on the milling jar and grinding balls and reducing contamination of the material by worn-off debris. Furthermore, it inhibits changes in diamond particle size during ball milling, facilitating precise control over diamond particle size.

[0059] For example, ball milling 2000-mesh diamond material with zirconia balls for 16 hours reveals the presence of zirconia in the milled material, and the diamond particle size is reduced to approximately 2500 mesh. However, ball milling diamond and ceramic binder together for 2 hours results in uneven mixing. If the ball milling time for the ceramic binder is less than 16 hours, such as 14 hours, the sintering activity of the material is insufficient, and the final sintering density decreases from 2.1 g / cm³. 3 Decrease of 1.8 g / cm 3 .

[0060] Typically, ceramic binders include SiO2, B2O3, Li2O, Na2O, Al2O3, TiO2, ZnO, and CaO. For example, the embodiments of this invention use a ceramic binder with SiO2 55-65 wt.%, Al2O3 5-10 wt.%, B2O3 10-15 wt.%, and Na2O / CaO 20-25 wt.%. Since diamond itself has relatively low heat resistance, the sintering temperature of ceramic-bonded diamond superhard materials is generally 600-900℃. Excessively high temperatures can cause diamond to graphitize, leading to performance degradation. This invention does not involve specific ceramic binder ratios; existing ceramic binder ratios can be used in the preparation method of this invention. During ball milling of the ceramic binder, dispersants and coupling agents are added simultaneously. Sodium hexametaphosphate and silane coupling agents are used in combination to treat the ceramic powder surface, achieving a comprehensive effect of synergistic dispersion, interface strengthening, and improved stability, preparing the material for subsequent mixing with organic binders.

[0061] This invention limits the mass ratio of diamond powder, ceramic binder, and organic binder solution to 1:(1-4):(0.5-2.5). This ratio is designed considering the particle size of different diamond powders, the printing effect of the slurry, and the application performance of the product. Since the organic binder decomposes and is eliminated during the debinding process, it will not remain in the final superhard material. Therefore, the ratio of diamond powder to ceramic binder is crucial for material performance and application. The 1:(1-4) ratio is determined based on the grinding requirements and the particle size of the diamond powder, and is proposed primarily for wafer thinning. When the diamond powder is fine, the proportions of the two are close; when the diamond powder is coarse, the proportion of diamond powder should be reduced. This helps improve the sharpness of coarse-grained diamond tools, reduce the load on the machining machinery, and achieve stable and reliable machining; it also helps improve the machining accuracy of fine-grained diamond tools and reduce the surface roughness. The proportion of organic binder is designed to ensure smooth printing while achieving good shape retention at the highest possible solids content.

[0062] (4) Adjusting viscosity: Heat the ball milling slurry from step (3) to 50-80℃ under a vacuum of 10-50 kPa, and take intermittent samples to test the viscosity until it reaches 3000-5000 Pa. . s, to obtain the printing paste;

[0063] In the previous steps (3) of the ceramic binder ball milling process and (2) of the organic binder preparation process, deionized water was added to ensure the progress of both steps. However, the ball milling slurry obtained in step (3) is relatively thin and cannot be used directly for printing. Some water needs to be removed to increase the viscosity. The simplest and most effective way is to heat and evaporate some of the water, but when the slurry is heated in the air, bubbles will be generated, making it difficult for the printing process to proceed smoothly and stably. Therefore, this invention proposes to heat and evaporate the water in a vacuum with a vacuum degree of 10-50 kPa. Too high a vacuum degree will cause a large number of bubbles to be generated, which will be difficult to eliminate after the viscosity is increased; too low a vacuum degree will result in a slow evaporation rate and will not have an obvious defoaming effect. Using a heating temperature of 50-80℃ is also in combination with the above vacuum degree to achieve the effect of evaporating water and defoaming. On the basis of meeting the above conditions, the viscosity of the slurry is adjusted to 3000-5000 Pa. . It can smoothly print out the designed workpiece shape. Figure 4 These are photographs of defective 3D-printed samples when the slurry viscosity is unsuitable. Figure (a) shows a sample with a lower viscosity of 2500 Pa. . s, the printed shape of the sample is difficult to maintain; the viscosity of Figure (b) is high, at 5500 Pa. . s, the slurry is difficult to extrude during the printing process.

[0064] (5) Printing and shaping: The slurry obtained in step (4) is fed into the ink direct writing 3D printer. The printing parameters are set as follows: nozzle diameter 0.5-0.8mm, printing speed 10-15mm / s, layer height 0.4-0.6mm, extrusion pressure 0.4-0.6MPa. The 3D printed porous structure model is printed layer by layer. After printing, it is placed in an environment with a relative humidity of 50-60% at 25-35℃ for 1-2 days. Then the humidity is adjusted to 35-45% and placed for another 1-2 days. Then the temperature is adjusted to 60-80℃ and dried for 1-2 days to complete the curing and obtain ceramic binder diamond printing green body.

[0065] First, the present invention relates to a 3D-printed porous structure workpiece, wherein the porous structure model is a cuboid or a cuboid curved into an arc shape. The porosity of the designed model is 30-70%. A porosity less than 30% results in insufficient workpiece strength, short lifespan, and poor durability. When the porosity is greater than 70%, the chip removal and heat dissipation effects of the pores are not significant. The preferred porosity is 40-60%, which provides sufficient strength and lifespan, as well as good chip removal and heat dissipation capabilities. The pore size of the 3D-printed porous structure model is 0.1-1.0 mm. If the pore size is too small, the chip removal and heat dissipation capabilities will be insufficient; if the pore size is too large, the strength will be insufficient. The preferred pore size is 0.3-0.7 mm. The printing path is along a direction at a 45-degree angle to the long side, and the paths of adjacent layers are perpendicular to each other, such as... Figures 6-10The sample block structure is shown. This tilting method ensures that each printed layer has the same angle as the rotary grinding direction during operation, guaranteeing consistent working conditions and stable operation. The dimensions of the porous structure model cuboid are: length 15-25mm, width 3-4mm, height 9-11mm, which are compatible with current thinning machines; the bending radius of the arc-shaped cuboid is 150mm or 100mm, corresponding to the commonly used 12-inch and 8-inch grinding wheels, respectively.

[0066] Input the designed workpiece model and the required printing parameters into the slicing software, slice it into a file that can drive the 3D printer to perform the task, import it into the 3D printer and prepare for printing. After loading the printing paste prepared in step (4) into the DIW printer's barrel, tighten the cap, start the air compressor to inject compressed air, and adjust the pressure to 0.4-0.6MPa through the air pressure regulating valve. After the paste is extruded from the nozzle, the 3D printer's printing program can be started to begin printing. The air pressure mainly depends on the viscosity of the paste in step (4). When the viscosity is high, a higher air pressure is used. In addition, the air pressure must also be matched with the printing parameters. When the printing speed is fast, the air pressure should also be high in order to speed up the extrusion of the paste; when the nozzle diameter is small, the resistance is large, so a higher air pressure should also be applied; when the layer height is large, a higher air pressure should also be used. In short, the air pressure is determined by the combined viscosity of the paste and the printing parameters.

[0067] Therefore, this invention involves a three-stage gradual drying and curing process for the printed green compact: first, it is placed in an environment of 25-35℃ and 50-60% relative humidity for 1-2 days to slowly evaporate some of the moisture; then, the humidity is adjusted to 35-45% and it is placed for another 1-2 days to continue evaporating some moisture; finally, the temperature is adjusted to 60-80℃ and dried for 1-2 days to completely dry and complete curing. This invention controls the slow evaporation of moisture through this process, ensuring uniform internal stress in the green compact and resulting in a printed green compact with a complete and defect-free appearance. This process and its parameters are closely related to the composition of the printing paste and the designed porous structure. After printing, the green compact has a high moisture content; directly placing it indoors to air dry for 3-5 days will cause cracking. Figure 5 As shown in (a), direct heating and curing in an oven will result in more severe consequences. If a two-stage drying and curing process is used after printing—first placing the print in an environment of 25-35℃ and 50-60% relative humidity for 1-2 days to slowly evaporate some moisture, and then adjusting the humidity to 35-45% and drying at 60-80℃ for 1-2 days to completely dry and cure—warping will occur. Figure 5 As shown in (b), the deformed shape leads to the scrapping of the green body. Therefore, a three-stage gradual drying and curing process is suitable for this invention.

[0068] (6) Degreasing and sintering: The green body from step (5) is placed in a high-temperature furnace and protected by nitrogen or argon. First, degreasing is performed at a heating rate of 2-5℃ / min. The temperature is raised to 500-550℃ and held for 2-4 hours to remove the binder in the green body. Then, sintering is performed at a heating rate of 3-5℃ / min. The temperature is raised to 600-900℃ and held for 1-2 hours. The temperature is then cooled to room temperature at a rate of 3-5℃ / min to obtain the porous ceramic bonded diamond superhard material finished product.

[0069] Organic binders are added during the 3D printing process to bind diamond powder and ceramic powder together to maintain the designed shape. However, this is detrimental to the final material properties and affects the high-temperature sintering process, thus requiring removal at low temperatures. This invention employs a thermal decomposition and sintering method, heating the dried and cured preform to 500-550℃ at a low heating rate of 2-5℃ / min. During this gradual heating, the organic binder is gradually decomposed and eliminated. As the temperature rises, residual moisture evaporates completely first, followed by the decomposition of glycerol, then HEC and HPMC, and finally silicone oil. Holding at 500-550℃ for 2-4 hours completely burns off the organic binder. The temperature is then further increased to the sintering temperature of 600-900℃ for 1-2 hours. The sintering temperature depends on the diamond particle size; higher sintering temperatures are used for coarser particles, and lower temperatures for finer particles. Additionally, the sintering temperature also depends on the melting point of the ceramic binder used; higher melting points require higher sintering temperatures. In summary, the conventional sintering temperature range is 600-900℃. Furthermore, to protect the diamond from high-temperature oxidation, an inert gas, such as nitrogen or argon, is required during sintering; nitrogen, being a lower-cost gas, is generally preferred. The cooling rate after sintering should not be too rapid, otherwise it may cause cracks or breakage.

[0070] This invention also relates to a wafer thinning wheel, which is obtained by bonding a rectangular block of 3D-printed porous ceramic-bonded diamond superhard material obtained by the preparation method described in this invention to an aluminum substrate with an adhesive, and then performing dimensional trimming and dynamic balancing after curing to obtain the wafer thinning wheel. For example, a 12-inch porous ceramic-bonded thinning wheel with a porosity of 50% made of 6000-mesh diamond (such as...) Figure 12 As shown, during grinding at the same operating current of approximately 13A, the feed rate can reach 0.6 μm / s (compared to 0.5 μm / s for conventional grinding wheels), and the service life can reach approximately 17,000 wafers (compared to approximately 14,000 wafers for conventional grinding wheels). This demonstrates that the wafer thinning grinding wheel of the present invention has good sharpness, high wear resistance, and a longer service life, thereby reducing wafer processing costs.

[0071] Taking the following specific embodiments of the present invention as an example: SiO2 60wt.%, Al2O3 6wt.%, B2O3 12wt.%, Na2O 12wt.%, CaO 10wt.%, silane coupling agent KH550, and polyether-modified silicone oil Dow Corning Q2-5211.

[0072] Example 1

[0073] (1) Dispersing diamond powder: 2000 mesh diamond powder was vacuum heated at 480℃ and 400 Pa for 40 min. A mixture of pure perchloric acid and nitric acid (volume ratio of pure perchloric acid to nitric acid of 4:1) with 6 times the mass of diamond powder was stirred at 200℃ for 4 h. After treatment, the powder was washed with water. In an ultrasonic dispersion device, 0.3 wt.% dispersant sodium hexametaphosphate, 0.3 wt.% silane coupling agent and 30 times the mass of diamond powder were added and ultrasonically dispersed for 40 min. Then the powder was filtered out.

[0074] (2) Preparation of organic binder solution: The water-based organic binder for 3D printing includes the main ingredient hydroxyethyl cellulose, the thickener hydroxypropyl methyl cellulose, the lubricant glycerin, the defoamer polyether modified silicone oil and deionized water. The concentrations of each component are 5.0 wt.%, 0.9 wt.%, 1.7 wt.%, 0.9 wt.%, and the remainder is deionized water.

[0075] (3) Ball milling slurry: 48 wt.% ceramic binder, 0.25 wt.% dispersant sodium hexametaphosphate, 0.9 wt.% silane coupling agent and deionized water (balance) were added to a mechanical ball mill and ball milled for 20 h; the diamond powder filtered out in step (1) was added to the ball-milled ceramic binder, the organic binder solution prepared in step (2) was added, and the ball milling was continued for another 1.5 h to obtain the ball milling slurry. The mass ratio of diamond powder, ceramic binder and organic binder solution was 1:2:2.

[0076] (4) Adjusting viscosity: Heat the ball milling slurry from step (3) to 50-80℃ under a vacuum of 10-50 kPa, and take intermittent samples to test the viscosity until it reaches 4800 Pa. . s, to obtain the printing paste;

[0077] (5) Printing and molding: The porosity of the 3D printed porous structure model is 50%, the pore size of the 3D printed porous structure model is 0.5mm, the hole structure model is a curved cuboid in the shape of an arc, the printing route is along the direction of 45 degrees with the long side, and the routes of the two adjacent layers are perpendicular to each other. The dimensions of the cuboid are: length 18mm, width 3.2mm, height 9.5mm, and the bending radius of the arc-shaped cuboid is 100mm. The slurry obtained in step (4) is fed into the ink direct writing 3D printer, and the printing parameters are set as follows: nozzle diameter 0.6mm, printing speed 12mm / s, layer height 0.5mm, extrusion pressure 0.5MPa. The porous structure model is printed layer by layer according to the preset model. After printing, it is placed in an environment with a relative humidity of 55% at 30℃ for 2 days, then the humidity is adjusted to 40% and placed for another 2 days, and then the temperature is adjusted to 70℃ and dried for 2 days to complete the curing, thus obtaining the ceramic binder diamond printing green body.

[0078] (6) Degreasing and sintering: The green body from step (5) is placed in a high-temperature furnace and protected with nitrogen or argon gas. Degreasing is performed first, with a heating rate of 3℃ / min, and the temperature is raised to 520℃ and held for 3 hours to remove the binder from the green body. Then, sintering is performed, with a heating rate of 4℃ / min, and the temperature is raised to 700℃ and held for 1 hour. The material is then cooled to room temperature at a rate of 4℃ / min to obtain the porous ceramic-bonded diamond superhard material product, such as… Figure 6 As shown.

[0079] Example 2

[0080] (1) Dispersing diamond powder: 300 mesh diamond powder was vacuum heated at 550℃ and 700Pa for 60 min. It was then stirred at 210℃ for 5 h with a mixture of pure perchloric acid and nitric acid (volume ratio 4:1) at 3 times the weight of the diamond powder. After treatment, it was washed with water. Then, 0.2 wt.% dispersant sodium hexametaphosphate, 0.2 wt.% silane coupling agent and 10 times the weight of water were added to the ultrasonic dispersion equipment based on the weight of the diamond powder and ultrasonically dispersed for 30 min. Then it was filtered out.

[0081] (2) Preparation of organic binder solution: The water-based organic binder for 3D printing includes the main ingredient hydroxyethyl cellulose, the thickener hydroxypropyl methyl cellulose, the lubricant glycerin, the defoamer polyether modified silicone oil and deionized water. The concentrations of each component are as follows: 2.0 wt.%, 0.5 wt.%, 1.2 wt.%, 0.6 wt.%, and the remainder is deionized water;

[0082] (3) Ball milling slurry: 55 wt.% ceramic binder, 0.5 wt.% dispersant sodium hexametaphosphate, 1.5 wt.% silane coupling agent and deionized water (balance) are added to a mechanical ball mill and ball milled for 16 h; diamond powder filtered out in step (1) is added to the ball-milled ceramic binder, the organic binder solution prepared in step (2) is added, and ball milling is continued for another 1 h to obtain ball milling slurry. The mass ratio of diamond powder, ceramic binder and organic binder solution is 1:4:0.5.

[0083] (4) Adjusting viscosity: Heat the ball milling slurry from step (3) to 80°C under a vacuum of 50 kPa, and take intermittent samples to test the viscosity until it reaches 5000 Pa. . s, to obtain the printing paste;

[0084] (5) Printing and molding: The porosity of the 3D printed porous structure model is 30%, the pore size of the 3D printed porous structure model is 1.0mm, the porous structure model is a cuboid, the printing route is along the direction of 45 degrees with the long side, the routes of the two adjacent layers are perpendicular to each other, the dimensions of the cuboid are: length 25mm, width 4mm, height 11mm; the slurry obtained in step (4) is sent into the ink direct writing 3D printer, and the printing parameters are set as follows: nozzle diameter 0.8mm, printing speed 15mm / s, layer height 0.6mm, extrusion pressure 0.4MPa. The porous structure model is printed layer by layer according to the preset porous structure model. After printing, it is placed at 25℃ and in an environment with a relative humidity of 50% for 1 day, then the humidity is adjusted to 35% and placed for another day, then the temperature is adjusted to 80℃ and dried for 1 day to complete the curing, and ceramic binder diamond printing green body is obtained;

[0085] (6) Degreasing and sintering: The green body from step (5) is placed in a high-temperature furnace and protected with nitrogen. Degreasing is performed first, with a heating rate of 5℃ / min, and the temperature is raised to 550℃ and held for 2 hours to remove the binder from the green body. Then, sintering is performed, with a heating rate of 5℃ / min, and the temperature is raised to 900℃ and held for 2 hours. The material is then cooled to room temperature at a rate of 5℃ / min to obtain the porous ceramic-bonded diamond superhard material product, such as… Figure 7 As shown.

[0086] Example 3

[0087] (1) Dispersing diamond powder: 1000 mesh diamond powder was vacuum heated at 520℃ and 400 Pa for 50 min. It was then stirred at 210℃ for 4 h with a mixture of pure perchloric acid and nitric acid (volume ratio 4:1) at 5 times the weight of the diamond powder. After treatment, it was washed with water. Then, 0.3 wt.% dispersant sodium hexametaphosphate, 0.3 wt.% silane coupling agent and 30 times the weight of water were added to the ultrasonic dispersion equipment based on the weight of the diamond powder and ultrasonically dispersed for 40 min. Then it was filtered out.

[0088] (2) Preparation of organic binder solution: The water-based organic binder for 3D printing includes the main ingredient hydroxyethyl cellulose, the thickener hydroxypropyl methyl cellulose, the lubricant glycerin, the defoamer polyether modified silicone oil and deionized water. The concentrations of each component are 3.0 wt.%, 0.6 wt.%, 1.4 wt.%, 0.7 wt.%, and the remainder is deionized water.

[0089] (3) Ball milling slurry: 52 wt.% ceramic binder, 0.4 wt.% dispersant sodium hexametaphosphate, 0.9 wt.% silane coupling agent and deionized water (balance) were added to a mechanical ball mill and ball milled for 18 h; the diamond powder filtered out in step (1) was added to the ball-milled ceramic binder, the organic binder solution prepared in step (2) was added, and the ball milling was continued for another 1 h to obtain the ball milling slurry. The mass ratio of diamond powder, ceramic binder and organic binder solution was 1:3:1.

[0090] (4) Adjusting viscosity: The ball milling slurry from step (3) is heated to 60°C under a vacuum of 20 kPa, and samples are taken intermittently to check the viscosity until it reaches 4500 Pa. . s, to obtain the printing paste;

[0091] (5) Printing and molding: The porosity of the 3D printed porous structure model is 40%, the pore size of the 3D printed porous structure model is 0.3mm, the porous structure model is a curved cuboid, the printing path is along the direction of 45 degrees with the long side, and the paths of the two adjacent layers are perpendicular to each other. The dimensions of the cuboid are: length 22mm, width 3.8mm, height 10.5mm, and the bending radius of the curved cuboid is 150mm; the slurry obtained in step (4) is fed into the ink direct writing 3D printer, and the printing parameters are set as follows: nozzle diameter 0.7mm, printing speed 14mm / s, layer height 0.5mm, extrusion pressure 0.55MPa. The porous structure model is printed layer by layer according to the preset porous structure model. After printing, it is placed at 30℃ and 60% relative humidity for 36 hours, then the humidity is adjusted to 45% and placed for another 36 hours, then the temperature is adjusted to 70℃ and dried for 36 hours to complete the curing, and the ceramic binder diamond printing green body is obtained;

[0092] (6) Debinding and sintering: The green body from step (5) is placed in a high-temperature furnace and protected with nitrogen gas. Debinding is performed first, with a heating rate of 4℃ / min, and the temperature is raised to 530℃ and held for 3 hours to remove the binder from the green body. Then, sintering is performed, with a heating rate of 4℃ / min, and the temperature is raised to 800℃ and held for 1.5 hours. The material is then cooled to room temperature at a rate of 5℃ / min to obtain a porous ceramic-bonded diamond superhard material, such as… Figure 8 As shown.

[0093] Example 4

[0094] (1) Dispersing diamond powder: 4000 mesh diamond powder was vacuum heated at 500℃ and 500 Pa for 45 min. It was then stirred at 200℃ for 5 h with a mixture of pure perchloric acid and nitric acid (volume ratio 4:1) equal to 8 times the weight of the diamond powder. After treatment, it was washed with water. Then, 0.35 wt.% dispersant sodium hexametaphosphate, 0.35 wt.% silane coupling agent and 40 times the weight of water were added to the ultrasonic dispersion equipment based on the weight of the diamond powder and ultrasonically dispersed for 45 min. Then it was filtered out.

[0095] (2) Preparation of organic binder solution: The water-based organic binder for 3D printing includes the main ingredient hydroxyethyl cellulose, the thickener hydroxypropyl methyl cellulose, the lubricant glycerin, the defoamer polyether modified silicone oil and deionized water. The concentrations of each component are 4.0 wt.%, 0.75 wt.%, 1.5 wt.%, 0.8 wt.%, and the remainder is deionized water.

[0096] (3) Ball milling slurry: 50 wt.% ceramic binder, 0.35 wt.% dispersant sodium hexametaphosphate, 1.2 wt.% silane coupling agent and deionized water (balance) are added to a mechanical ball mill and ball milled for 20 h; diamond powder filtered out in step (1) is added to the ball-milled ceramic binder, the organic binder solution prepared in step (2) is added, and ball milling is continued for another 2 h to obtain ball milling slurry. The mass ratio of diamond powder, ceramic binder and organic binder solution is 1:2.5:1.5.

[0097] (4) Adjusting viscosity: The ball milling slurry from step (3) is heated to 70°C under a vacuum of 30 kPa, and samples are taken intermittently to test the viscosity until it reaches 4000 Pa. . s, to obtain the printing paste;

[0098] (5) Printing and molding: The porosity of the 3D printed porous structure model is 60%, the pore size of the 3D printed porous structure model is 0.7mm, the porous structure model is a cuboid, the printing route is along the direction of 45 degrees with the long side, the routes of the two adjacent layers are perpendicular to each other, the dimensions of the cuboid are: length 20mm, width 3.5mm, height 10mm, the slurry obtained in step (4) is sent into the ink direct writing 3D printer, the printing parameters are set: nozzle diameter 0.6mm, printing speed 12mm / s, layer height 0.5mm, extrusion pressure 0.5MPa, the porous structure model is printed layer by layer according to the preset porous structure model, after printing, it is placed at 30℃ and 60% relative humidity for 1 day, then the humidity is adjusted to 45% and placed for another day, then the temperature is adjusted to 70℃ and dried for 2 days to complete the curing, and the ceramic binder diamond printing green body is obtained;

[0099] (6) Degreasing and sintering: The green body from step (5) is placed in a high-temperature furnace and protected with nitrogen gas. Degreasing is performed first, with a heating rate of 3℃ / min, and the temperature is raised to 520℃ and held for 3 hours to remove the binder from the green body. Then, sintering is performed, with a heating rate of 4℃ / min, and the temperature is raised to 700℃ and held for 1.5 hours. The material is then cooled to room temperature at a rate of 4℃ / min to obtain the porous ceramic-bonded diamond superhard material product, such as… Figure 9 As shown.

[0100] (7) The porous ceramic-bonded diamond superhard material with a curved rectangular shape obtained in step (6) is bonded to an 8-inch aluminum substrate with epoxy resin. After curing, the 8-inch thinning grinding wheel is obtained by trimming the dimensions and dynamic balancing. Figure 11 As shown in the figure. Figure (a) shows the original thinning grinding wheel, and Figure (b) shows a magnified view of the edge of the thinning grinding wheel. The service life of the thinning grinding wheel is 18,000-20,000 8-inch silicon wafers, and the surface roughness Ra of the processed wafers is 8-10 nm.

[0101] Example 5

[0102] (1) Dispersing diamond powder: 6000 mesh diamond powder was vacuum heated at 450℃ and 300 Pa for 30 min. It was then stirred at 200℃ for 4 h with a mixture of pure perchloric acid and nitric acid (volume ratio 4:1) 10 times the weight of the diamond powder. After treatment, it was washed with water. In an ultrasonic dispersion device, 0.5 wt.% dispersant sodium hexametaphosphate, 0.5 wt.% silane coupling agent and 50 times the weight of water were added based on the weight of the diamond powder and ultrasonically dispersed for 60 min. Then it was filtered out.

[0103] (2) Preparation of organic binder solution: The water-based organic binder for 3D printing includes the main ingredient hydroxyethyl cellulose, the thickener hydroxypropyl methyl cellulose, the lubricant glycerin, the defoamer polyether modified silicone oil and deionized water, with the concentrations of each component being 6.0 wt.%, 1.0 wt.%, 1.8 wt.%, and 1.0 wt.%, respectively, and the remainder being deionized water;

[0104] (3) Ball milling slurry: 45 wt.% ceramic binder, 0.2 wt.% dispersant sodium hexametaphosphate, 0.8 wt.% silane coupling agent and deionized water (balance) were added to a mechanical ball mill and ball milled for 24 h; the diamond powder filtered out in step (1) was added to the ball-milled ceramic binder, the organic binder solution prepared in step (2) was added, and the ball milling continued for another 2 h to obtain the ball milling slurry. The mass ratio of diamond powder, ceramic binder and organic binder solution was 1:1:2.5.

[0105] (4) Adjusting viscosity: Heat the ball milling slurry from step (3) to 50°C under a vacuum of 10 kPa, and take intermittent samples to test the viscosity until it reaches 3000 Pa. .s, to obtain the printing paste;

[0106] (5) Printing and molding: The porosity of the 3D printed porous structure model is 70%, the pore size of the 3D printed porous structure model is 0.1m, the porous structure model is a cuboid, the printing route is along the direction of 45 degrees with the long side, the routes of the two adjacent layers are perpendicular to each other, the dimensions of the cuboid are: length 15m, width 3mm, height 9mm; the slurry obtained in step (4) is sent into the ink direct writing 3D printer, and the printing parameters are set as follows: nozzle diameter 0.5mm, printing speed 10mm / s, layer height 0.4mm, extrusion pressure 0.4MPa. The porous structure model is printed layer by layer according to the preset porous structure model. After printing, it is placed at 35℃ and in an environment with a relative humidity of 60% for 2 days. Then the humidity is adjusted to 45% and placed for another 2 days. Then the temperature is adjusted to 60℃ and dried for 2 days to complete the curing and obtain ceramic binder diamond printing green body;

[0107] (6) Debinding and sintering: The green body from step (5) is placed in a high-temperature furnace and protected with argon gas. Debinding is performed first, with a heating rate of 2℃ / min, and the temperature is raised to 500℃ and held for 2 hours to remove the binder from the green body. Then, sintering is performed, with a heating rate of 3℃ / min, and the temperature is raised to 600℃ and held for 1 hour. The material is then cooled to room temperature at a rate of 3℃ / min to obtain the porous ceramic-bonded diamond superhard material product, such as… Figure 10 As shown.

[0108] (7) The porous ceramic-bonded diamond superhard material product with a curved rectangular shape obtained in step (6) is bonded to a 12-inch aluminum substrate with epoxy resin. After curing, the 12-inch thinning grinding wheel is obtained by trimming the dimensions and dynamic balancing. Figure 12 As shown in the figure. Figure (a) shows the original thinning grinding wheel, and Figure (b) shows a magnified view of the edge of the thinning grinding wheel. The service life of the thinning grinding wheel is 16,000-18,000 12-inch silicon wafers, and the surface roughness Ra of the processed wafers is 9-12 nm.

[0109] Comparative Example 1

[0110] In step 2, the aqueous organic binder used for 3D printing includes the main ingredient hydroxyethyl cellulose (HEC), the thickener hydroxypropyl methyl cellulose (HPMC), the lubricant glycerin, the defoamer polyether-modified silicone oil, and deionized water. The concentrations of each component are 7.0 wt.%, 0.4 wt.%, 1.5 wt.%, and 0.8 wt.%, with the remainder being deionized water. Other process steps and parameters are the same as in Example 5 of this invention. The resulting porous ceramic-bonded diamond superhard material is as follows: Figure 13 As shown.

[0111] Due to an inappropriate ratio of HEC and HPMC, with too much HEC (2.0-6.0 wt.%) exceeding the scope of this invention and too little HPMC (0.5-1.0 wt.%) below the scope of this invention, the extruded fibers expand after the slurry is extruded, leading to pore blockage. The pore size and porosity cannot match the design model.

[0112] Comparative Example 2

[0113] In step 2, the aqueous organic binder used for 3D printing includes the main ingredient hydroxyethyl cellulose, the thickener hydroxypropyl methyl cellulose, the lubricant glycerin, the defoamer polyether-modified silicone oil, and deionized water. The concentrations of each component are 1.0 wt.%, 2.0 wt.%, 1.5 wt.%, and 0.8 wt.%, with the remainder being deionized water. Other process steps and parameters are the same as in Example 5 of this invention. The resulting porous ceramic-bonded diamond superhard material is as follows: Figure 14 As shown.

[0114] Due to an inappropriate ratio of HEC and HPMC, with too little HEC (below the range of this invention, 2.0-6.0 wt.%) and too much HPMC (beyond the range of this invention, 0.5-1.0 wt.%), the extruded filaments have high viscosity and insufficient extrusion after slurry extrusion. The dragging of the extruded filaments also causes the pore size and porosity to be unable to match the design model.

[0115] Comparative Example 3

[0116] Step (1) Dispersing diamond powder: 6000-mesh diamond powder was stirred at 200℃ for 4 h with a mixture of perchloric acid and nitric acid (volume ratio 4:1). After treatment, it was washed with water, and 0.5 wt.% dispersant sodium hexametaphosphate and 0.5 wt.% silane coupling agent were added and ultrasonically dispersed for 60 min. Then it was filtered out. The remaining steps were the same as in Example 5 of this invention. The thinned grinding wheel prepared in the end has a service life of 12,000-14,000 wafers under the same processing conditions when grinding 12-inch silicon wafers, and the surface roughness Ra of the processed wafers is 16-19 nm.

[0117] Compared with Example 5, Comparative Example 3 did not involve vacuum heating, so the diamond surface could not be activated through micro-oxidation, resulting in a shorter lifespan for the processed silicon wafers and a higher surface roughness.

[0118] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for 3D printing a porous ceramic-bonded diamond superhard material, characterized in that, The preparation method includes the following steps: (1) Dispersing diamond powder: The diamond powder is vacuum heated at a temperature of 450-550℃ and a vacuum degree of 300-700Pa for 30-60 minutes. It is stirred with a mixed acid containing perchloric acid and nitric acid at 200-210℃ for 4-5 hours. After treatment, it is washed with water. Based on the weight of the diamond powder, 0.2-0.5wt.% of dispersant sodium hexametaphosphate, 0.2-0.5wt.% of silane coupling agent and 10-50 times the amount of water are added. The mixture is ultrasonically dispersed for 30-60 minutes and then filtered out to obtain dispersed diamond powder. (2) Preparation of organic binder solution: The main ingredient hydroxyethyl cellulose, the thickener hydroxypropyl methyl cellulose, the lubricant glycerin and the defoamer polyether modified silicone oil are added to deionized water and dispersed evenly to obtain a water-based organic binder for 3D printing. (3) Ball milling slurry: Add 45-55 wt.% ceramic binder, 0.2-0.5 wt.% dispersant sodium hexametaphosphate, 0.8-1.5 wt.% silane coupling agent and the balance deionized water to a mechanical ball mill and ball mill for 16-24 h to obtain ball milling material; add the diamond powder filtered out in step (1) to the ball milling material, add the organic binder solution prepared in step (2), and continue ball milling for 1-2 h to obtain ball milling slurry; (4) Adjusting viscosity: After adjusting the viscosity of the ball mill slurry from step (3) by vacuum heating, printing slurry is obtained; (5) Printing and shaping: The printing paste obtained in step (4) is fed into the ink direct writing 3D printer. The printing parameters are set as follows: nozzle diameter 0.5-0.8mm, printing speed 10-15mm / s, layer height 0.4-0.6mm, extrusion pressure 0.4-0.6MPa. The printing is carried out layer by layer according to the preset 3D printing porous structure model. After printing, it is placed in an environment with a relative humidity of 50-60% at 25-35℃ for 1-2 days. Then the humidity is adjusted to 35-45% and placed for another 1-2 days. Then the temperature is adjusted to 60-80℃ and dried for 1-2 days to complete the curing and obtain ceramic binder diamond printing green body. (6) Degreasing and sintering: The green blank from step (5) is placed in a high-temperature furnace and protected by nitrogen or argon. First, degreasing is performed, and the temperature is raised to 500-550℃ at a heating rate of 2-5℃ / min and held for 2-4 hours. Then, sintering is performed, and the temperature is raised to 600-900℃ at a heating rate of 3-5℃ / min and held for 1-2 hours. Then, the temperature is cooled to room temperature at a rate of 3-5℃ / min to obtain the porous ceramic bonded diamond superhard material finished product.

2. The 3D printing preparation method of porous ceramic-bonded diamond superhard material according to claim 1, characterized in that, In step (1), the diamond powder has a particle size of 300 mesh or more, preferably 2000 mesh or more; And / or, in step (1), the mixed acid contains both perchloric acid and nitric acid as pure acids, with a volume ratio of 4:1, and the mass of the mixed acid is 3-10 times the mass of the diamond powder.

3. The 3D printing preparation method of porous ceramic-bonded diamond superhard material according to claim 1, characterized in that, In step (2), the mass concentration of each component in the water-based organic binder is as follows: 2.0-6.0 wt.% hydroxyethyl cellulose, 0.5-1.0 wt.% hydroxypropyl methyl cellulose, 1.2-1.8 wt.% glycerol, 0.6-1.0 wt.% polyether modified silicone oil, and the balance is deionized water.

4. The 3D printing preparation method of porous ceramic-bonded diamond superhard material according to claim 1, characterized in that, In step (3), the mass ratio of diamond powder, ceramic binder and organic binder solution in the ball milling slurry is 1: (1-4): (0.5-2.5).

5. The 3D printing preparation method of porous ceramic-bonded diamond superhard material according to claim 1, characterized in that, In step (4), the vacuum heating conditions are: heating the ball mill slurry to 50-80℃ under a vacuum of 10-50kPa.

6. The 3D printing preparation method of porous ceramic-bonded diamond superhard material according to claim 1, characterized in that, In step (4), the ball milling slurry from step (3) is vacuum heated, and samples are taken intermittently to test the viscosity, which reaches 3000-5000 Pa. . s, to obtain the printing paste.

7. The 3D printing preparation method of porous ceramic-bonded diamond superhard material according to claim 1, characterized in that, In step (5), the porosity of the 3D printed porous structure model is 30-70%, preferably 40-60%; the pore size of the 3D printed porous structure model is 0.1-1.0 mm, preferably 0.3-0.7 mm.

8. The 3D printing preparation method of porous ceramic-bonded diamond superhard material according to claim 1, characterized in that, In step (5), the 3D printed porous structure model is a cuboid or a cuboid curved into an arc shape, and the printing path is along a direction at a 45-degree angle to the long side, with the paths of two adjacent layers being perpendicular to each other. Preferably, the dimensions of the cuboid are: length 15-25mm, width 3-4mm, height 9-11mm, and the bending radius of the arc-shaped cuboid is 150mm or 100mm.

9. The porous ceramic-bonded diamond superhard material prepared by the method according to any one of claims 1 to 8.

10. A wafer thinning grinding wheel, characterized in that, It is obtained by bonding the porous ceramic binder diamond superhard material of claim 9 to an aluminum substrate with an adhesive, and then adjusting the size and dynamic balance after curing.